Additive manufacturing of a single crystal nickel-based superalloy using selective electron beam melting - Chandra, Shubham (2018)
Single crystal (SX) nickel-based superalloy blade forms a key element of hightemperature gas turbines that are vital to aviation and power industries, owing to its excellent creep properties at elevated temperatures. Conventional manufacturing of SX Ni-based superalloy components is a tedious and expensive process due to stringent tolerance on part geometry and SX quality. Additive manufacturing (AM) provides unique features such as economic sustainability, automated manufacturing process and capability of printing identical parts. Moreover, the future of AM technologies shows significant promise towards achieving complete layer-wise control, in terms of varying process parameters. This study employs selective electron beam melting (SEBM), a powder-bed metal AM technique, to additively manufacture a first-generation Nickel-based SX superalloy. High vacuum environment and nearly unidirectional thermal gradient, inherent with SEBM, make it the most promising AM technique for SX superalloy manufacturing. Detailed microstructural characterization using optical microscopy, scanning electron microscopy and X-ray diffraction reveal that dominant columnar grains aligned with the build direction were formed into a strongly textured superalloy sample. However, there are still some cracks occurred along the columnar grain boundaries. The correlation between SEBM processing and microstructure is discussed.